2020
DOI: 10.1021/acs.jnatprod.0c00263
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Networking-Guided Discovery and Characterization of Stechlisins, a Group of Cyclic Lipopeptides from a Pseudomonas sp.

Abstract: Increasingly sensitive analytical instruments and robust downstream data processing tools have revolutionized natural product research over the past decade. A molecular networking-guided survey led to the identification of 33 new cyclic lipopeptides (CLPs) from the culture broth of the proteobacterium Pseudomonas sp. FhG100052. The compound family resembles members of the amphisin group of CLPs that possess a 3-hydroxy fatty acid linked to the N-terminus of an undecapeptide core. Culture optimization led to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…A visualization of the network was constructed in Cytoscape v3.6.0. 46 Edges were drawn between scan nodes with a cosine similarity >0.7 47 . Samples were dissolved in 100 µL H2O, derivatized with L-FDVA and analyzed using the same parameters as described before.…”
Section: Resultsmentioning
confidence: 99%
“…A visualization of the network was constructed in Cytoscape v3.6.0. 46 Edges were drawn between scan nodes with a cosine similarity >0.7 47 . Samples were dissolved in 100 µL H2O, derivatized with L-FDVA and analyzed using the same parameters as described before.…”
Section: Resultsmentioning
confidence: 99%
“…While these results indicate a generally robust transfer of primarily observed growth inhibitory effects to microfractionated assays, two extracts did not show bioactivity in any fraction. These findings emphasize a general challenge in bioactivity driven NP research (in contrast to cheminformatics inclined discovery projects [38]): Microbial crude extracts are composed of a mixture of various substances at dramatically different concentrations and potencies. It is important to realize that almost each substance (or a combination of several metabolites) becomes unspecifically toxic at high concentrations, hence producing a positive assay read out.…”
Section: Discussionmentioning
confidence: 81%
“…MSConvert (ProteoWizard package32) was used to convert the raw data (*.d files) into plain text (*.mgf) files, wherein all detected fragment ions are expressed as a list of mass/intensity value pairs sorted according to their parent ions (peak picking: vendor MS level = 1-2; threshold type = absolute intensity, value = 1000, orientation = most-intense). The networking algorithm itself, thus the calculation of cosine similarity values between parent ion vectors, was computed offline, using an in house server [38].…”
Section: Molecular Networkingmentioning
confidence: 99%
“…The accession numbers for NRPS genes and PleB and PvdT homologs are provided in Table S1. Tensin congeners produced by strain FhG100052 were designated stechlisins ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…LPs are also involved in important ecological functions, such as swarming motility, biofilm formation, phytopathogenicity, cooperation, or antagonism ( 3 5 ). In recent years, research on Pseudomonas LPs has grown rapidly and many studies reported new producer strains of known LPs as well as the characterization of new LPs among single or large sets of environmental Pseudomonas isolate(s) ( 6 10 ). The initial detection of LP producer strains often relies on phenotypical tests (e.g., surfactant, antagonistic, or hemolytic activities) or on DNA amplification targeting conserved catalytic domains in their biosynthetic enzymes, complemented with analytical chemistry methodologies (e.g., liquid chromatography-mass spectrometry [LC-MS]).…”
Section: Introductionmentioning
confidence: 99%